Cocoa Research Institute : annual report 1976/77-1978/79 - Cocoa Research Institute (Ghana) (Tafo : Cocoa Research Institute, 1984)
The book contains the report of the activities of Cocoa Research Institute of Ghana for the period of 1976/77-1978/79.
usc 21/02/2019
Ref
Keywords: Cocoa--Research; Cocoa--Breeding; Africa, West; Ghana